2001
DOI: 10.1016/s0375-9474(01)00679-0
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear reaction rates and the nova outburst

Abstract: Classical novae participate in the cycle of Galactic chemical evolution in which grains and metal enriched gas in their ejects, supplementing those of supernovae, AGB stars, and WR stars, are a source of heavy elements for the ISM. Once in the diffuse gas, this material is cycled through molecular clouds before being incorporated into young stars and planetary systems during star formation. Infrared observations have confirmed the presence of carbon, SiC, hydrocarbons, and oxygen-rich silicate grains in nova e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 3 publications
2
7
0
Order By: Relevance
“…In fact, the reduction of the proton capture rate halts significantly the synthesis of elements above Si (by a factor of ∼ 10 with respect to the values found with the nominal rate). We have compared our results with the latest available results from hydrodynamic simulations of ONe novae by Starrfield et al (2001): they state that the switch to an updated nuclear network (Iliadis et al 2001) is accompanied by an important reduction of the abundances of nuclei above aluminum, in good agreement with the results found here. However, our new computations show that reduction of the yields affect only nuclei above 32 S. In fact, a significant reduction of 32 S results only when we adopt the low 30 P(p,γ) test rate.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…In fact, the reduction of the proton capture rate halts significantly the synthesis of elements above Si (by a factor of ∼ 10 with respect to the values found with the nominal rate). We have compared our results with the latest available results from hydrodynamic simulations of ONe novae by Starrfield et al (2001): they state that the switch to an updated nuclear network (Iliadis et al 2001) is accompanied by an important reduction of the abundances of nuclei above aluminum, in good agreement with the results found here. However, our new computations show that reduction of the yields affect only nuclei above 32 S. In fact, a significant reduction of 32 S results only when we adopt the low 30 P(p,γ) test rate.…”
Section: Resultssupporting
confidence: 83%
“…Hence, this discrepancy might be likely attributed to a different prescription for the adopted 30 P(p,γ) rate. In particular, the rate used by Starrfield et al (2001) seems to be somewhat lower than the nominal rate adopted in our paper, which stresses again the crucial dependence of the S-Ca yields on this particular rate.…”
Section: Resultsmentioning
confidence: 42%
“…This range in ejected mass is unexpected if WD mass is the primary controlling variables. However, new theoretical models of Starrfield et al (2000Starrfield et al ( , 2001 and Yaron et al (2005) show that the ejected mass is also dependent on variables such as the initial composition of the accreted shell, the WD temperature, and the accretion rate. Whether the low initial WD luminosities ($10 À3 L ) and mass accretion rates ( 10 À10 M yr À1 ) required by the models is typical for classical nova remains to be seen.…”
Section: Discussionmentioning
confidence: 99%
“…A discussion of the improvements is provided in S1998. The third library (labeled I2001) is described in Iliadis et al (2001) and was used for the simulations reported in Starrfield et al (2001). The fourth library (labeled I2005A) is the August 2005 library of Iliadis and the results of calculations done with this library are given in this paper.…”
Section: The Hydrodynamic Computer Code and Nuclear Reaction Rate Libmentioning
confidence: 99%